16.7k views
2 votes
Simplify these expressions. a.2r+3+4r. b.8+3d+d. c.mn+ (-3mm)+6 d. 10s + (-10) + (-4s)

User Akelec
by
5.8k points

2 Answers

1 vote

Answer:

a. 2r + 3 + 4r

Combine the coefficients of the like monomials.

(2 + 4 = 6)

Answer: 6r + 3

b. 8 + 3d + d

Combine the coefficients of the like monomials.

(3 + 1 = 4)

Answer: 8 + 4d

c. mn + (–3mn) + 6

Combine the coefficients of the like monomials.

[1 + (–3) = –2]

Answer: –2mn + 6

d. 10s + (–10) + (–4s)

Combine the coefficients of the like monomials.

[10 + (–4) = 6]

Answer: 6s + (–10)

Explanation:

straight from Penn

User Loheek
by
5.7k points
3 votes

Explanation:

Combine like terms

a. 2r + 3 + 4r = (2r + 4r) + 3 = 6r + 3

b. 8 + 3d + d = (3d + d) + 8 = 4d + 8

c. mn + (-3mn) + 6 = (mn - 3mn) + 6 = -2mn + 6

d. 10s + (-10) + (-4s) = (10s - 4s) - 10 = 14s - 10

Terms are called "like terms" if they have the same variable part (the same letters in the same powers). Like terms differ at most coefficient.

User Neeraj Singh
by
6.9k points